2020
DOI: 10.1111/jcmm.15902
|View full text |Cite
|
Sign up to set email alerts
|

YAP accelerates vascular senescence via blocking autophagic flux and activating mTOR

Abstract: Senescence, one of the main risk factors contributing to vascular dysfunction and the progression of vascular diseases, 1,2 is characterized by the gradual decline in physiological functions occurring at both cellular and organic levels. 3 Cellular senescence is known as replicative senescence, with an irreversible cell cycle arrest characteristic, while organic senescence is a kind of reduced stress response and increases homoeostatic imbalance, resulting in a variety of disorders, including cardiovascular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…[14,15] In aged-vascular tissue, YAP is highly expressed, and inhibition and knockdown of YAP reduce senescence, whereas overexpression of YAP enhances senescence in both vascular endothelial cells and vascular tissues. [16] Additionally, YAP is known as a "mechano-sensor" because of its ability to recognize mechanical microenvironments. [17] For instance, cultured cells can sense the stiffness of cell-adhesive gels: stiff gels that mimic aged tissues promote nuclear YAP localization, whereas soft gels that mimic young tissues promote cytoplasmic YAP localization.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] In aged-vascular tissue, YAP is highly expressed, and inhibition and knockdown of YAP reduce senescence, whereas overexpression of YAP enhances senescence in both vascular endothelial cells and vascular tissues. [16] Additionally, YAP is known as a "mechano-sensor" because of its ability to recognize mechanical microenvironments. [17] For instance, cultured cells can sense the stiffness of cell-adhesive gels: stiff gels that mimic aged tissues promote nuclear YAP localization, whereas soft gels that mimic young tissues promote cytoplasmic YAP localization.…”
Section: Introductionmentioning
confidence: 99%
“…By far, whether PLAU causes cellular senescence has not been reported in the existing studies. YAP upregulates the expression of PLAU [ 39 ], and YAP promotes senescence in both endothelial cells and smooth muscle cells [ 40 ], suggesting that PLAU may serve as a downstream molecule, contributing to YAP-induced vascular cell senescence. However, in another study on glioma cells, glioblastoma cells, and astrocytes, it was shown that YAP prevents senescence induced by several factors [ 41 , 42 ], and in cancer cells, PLAU accelerates proliferation [ 39 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The figure was obtained using PathFindR from the R package [Colour figure can be viewed at wileyonlinelibrary.com] activity reduces senescence while its overexpression enhances senescence in both vascular endothelial cells and vascular tissues. 48 Moreover, modulation of YAP localization (i.e., cytoplasmic or nuclear) was shown to delay senescence of vascular endothelial cells through subcellular YAP localization. 49 Further studies will be needed to clarify the mechanisms by which the Hippo signaling pathway affects endothelial homeostasis.…”
Section: Discussionmentioning
confidence: 99%